Health-related Consequences of Traumatic Brain Injury: A Scoping Review - Thaiudom, Ann; Dean-Baar, Susan (Journal of The Royal Thai Army Nurses, 2022)
Traumatic brain injury (TBI) is a global public health issue, causing tremendous healthcare and economic burden. The purpose of this review is to examine the consequences of TBI on individuals’ health across all levels of severity to guide nursing practice and future research. This review looks at the entire continuum of TBI. A total of 24 studies that met the inclusion criteria were included in this review. The results show that TBI had adverse effects on individuals’ physical, cognitive, psychosocial, and behavioral health. This review also found that repetitive TBI, which complicates the consequences and delays the brain healing process, is not adequately addressed. Supportive interventions for persons with TBI to deal with these challenges after TBI is essential. Symptom management, social support, problem-solving skills, healthy lifestyle interventions, and repetitive injury prevention for TBI patients should be top priorities for nursing research, education, and clinical practice.